Using Humans, Mobile Devices and Multiples Sensors for Localization of People Indoor - Lima, Luis Gustavo Cardoso; Marques Neto, Manoel Carvalho; Novais, Renato Lima (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2017)
Monitoring environments is a increasing need in different contexts, such as emergency, safety and health. Obtaining the location of people and setting the best route to evacuate a burning building; restrict access to an environment only to authorized people; or monitoring seniors or people in medical treatment in their homes are necessities in these three contexts. Thus, monitoring by identifying and locating people indoors is still a nontrivial task considered by some as an open challenge. The difficulties in identify and locate people result from the lack of precision of the various sensors and the cost to getting it. This project aims to develop a solution based not only on the usual sensors but also through the collaboration of people as sensors to help detect other people. The objective of this paper is to show that the human factor can be the difference in increased precision of identification and detection systems people in indoor environments.